PENGEMBANGAN MEDIA BELAJAR AKUNTANSI DENGAN MODUL BERBASIS PROJECT UNTUK PEMBELAJARAN JARAK JAUH DI SMK PGRI 3 KEDIRI - Sudarsono, Regal Wahyu (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This study aims to determine the effect of learning media using project-based modules for distance learning, the method used in this study focuses on the project module which contains basic introductory accounting material with examples and project assignments for X AKL students. This research uses descriptive quantitative with multiple regression, determinant coefficient and hypothesis testing. From the data obtained from students, the results are (1) data analysis of learning media variables on learning outcomes with a value of sig 0.001 < 0.05, project module variables on learning outcomes with a value of sig 0.001 < 0.05 and (3) distance learning variables on learning outcomes sig 0.001 < 0.05. In the veliabel, for the multiple coefficient test (R Square) it is worth 0.617 that all the variables studied affect 62% with strong status, in the F test all variables get a value of <0.05 which states that all variables have a significant influence.